2018
DOI: 10.1136/bmjpo-2018-000269
|View full text |Cite
|
Sign up to set email alerts
|

Newborn biliary atresia screening with the stool colour card: a questionnaire survey of parents

Abstract: PurposeBiliary atresia can easily be screened using a stool colour card (SCC) and has shown to significantly reduce time to diagnosis, improving children’s outcome. Despite the general approval of the clinical usefulness of the SCC, physicians remain reluctant: it might unnecessarily worry parents. This study aimed to analyse the parental reaction to this screening method and if it evokes parental stress.MethodsA semistructured questionnaire was sent to parents with one or more healthy child to inquire about r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
0
12
0
5
Order By: Relevance
“…Furthermore, attending pediatricians argued that SCC could unsettle parents, leading to numerous presentations in out-patient clinics and potentially resulting in unnecessary diagnostics. However, the authors in Borgeat et al recently presented the results of a survey of parents, showing that the vast majority considered the SCC helpful and simple, while only the minority reported on uneasiness using the SCC [ 20 ]. While the study group from Geneva faced similar reservations of Swiss physicians, blaming the SCC for parents anxiety, the authors concluded the exact opposite, emphasizing the benefits of an SCC screening [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, attending pediatricians argued that SCC could unsettle parents, leading to numerous presentations in out-patient clinics and potentially resulting in unnecessary diagnostics. However, the authors in Borgeat et al recently presented the results of a survey of parents, showing that the vast majority considered the SCC helpful and simple, while only the minority reported on uneasiness using the SCC [ 20 ]. While the study group from Geneva faced similar reservations of Swiss physicians, blaming the SCC for parents anxiety, the authors concluded the exact opposite, emphasizing the benefits of an SCC screening [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, in Japan, Taiwan, the Mainland of China, The Netherlands, Switzerland, German and Canada an original edition of SCC except for the Mainland of China was used (Matsui and Dodoriki 1995;Hsiao et al 2008;Kong et al 2016;Witt et al 2016;Borgeat et al 2018;Madadi-Sanjani et al 2019;Masucci et al 2019). The feasibility of screening has not been assessed or reported except that in Japan, Taiwan and the Mainland of China.…”
Section: Discussionmentioning
confidence: 99%
“…National BA screening programs using an SCC have been introduced in Switzerland and Japan [36,49]. Small pilot studies with the SCC have been conducted in regions or municipalities in Brazil [50], Cairo, Egypt [51], Shenzen (China) [52], Northern Portugal [53], and Lower Saxony Germany [54].…”
Section: Ba Screening Using a Stool Color Cardmentioning
confidence: 99%